Optimization of Ferroelectric Properties of HfO2-Based Thin Films by Ion Irradiation - Liao, Ningtao; Lin, Xin; Zhu, Bingyan; Zhong, Xiangli; Jiang, Limei; Ouyang, Xiaoping (IEEE transactions on nuclear science, 2024)
In order to explore ion irradiation optimization schemes for HfO2-based ferroelectric films, this article combines the Monte Carlo (MC) method with the phase-field method to establish a multiscale model that correlates micro vacancy and macro ferroelectric properties of thin films. This study indicates that ions, such as He, Ar, and Fe, can optimize the ferroelectric properties of thin films, while H ions are unsuitable for irradiation optimization. The synergistic effect of concentration and distribution of ion-induced ion oxygen vacancies is the key microscopic factor affecting the film's ferroelectric properties. Oxygen vacancy defects with a concentration of 1× 10^{22} cm3 and uniform distribution could maximize the optimization of thin film's ferroelectric performance. Oxygen vacancy's concentration and distribution are, respectively, mainly determined by the ion dose and type. Adjusting the incidence angle of ion can, to some extent, solve the problem of uneven distribution of oxygen vacancies. Through extensive simulation analysis, we found that Ar ions, when administered at an incidence energy of 400 keV and dosage of 5× 10^{15} ions/cm2, exhibit the most significant optimization effect on the ferroelectric properties of the thin film, resulting in a remarkable 46% increase in remanent polarization compared to the pre-irradiation state. This work elucidates the fundamental principles of optimizing the ferroelectric properties of HfO2-based thin films by ion irradiation and provides appropriate irradiation conditions, thus offering theoretical support for experimental endeavors in ion irradiation-based modification and optimization.